2015
DOI: 10.1111/jasp.12354
|View full text |Cite
|
Sign up to set email alerts
|

Desirable but not smart: preference for smarter romantic partners impairs women's STEM outcomes

Abstract: Although women today excel in many areas of society, they are often underrepresented in the traditionally male-dominated fields of Science, Technology, Engineering, and Math (STEM). The present research examined whether traditional romantic partner preferences-specifically, a desire to date partners who are smarter than oneself-affects women's tendency to minimize their intelligence in STEM fields when pursuing romantic goals. Women (but not men) who preferred smarter romantic partners showed worse math perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The researchers considered this preference to be reflection of internalized traditional gender norms. Indeed, when the goal of being romantically desirable was activated, women who showed preference for smarter mates reported less interest in STEM careers (Park et al, 2016).…”
Section: The Cultural Construction Of Academic Choicementioning
confidence: 99%
“…The researchers considered this preference to be reflection of internalized traditional gender norms. Indeed, when the goal of being romantically desirable was activated, women who showed preference for smarter mates reported less interest in STEM careers (Park et al, 2016).…”
Section: The Cultural Construction Of Academic Choicementioning
confidence: 99%
“…Similar positive effects of intergroup contact are seen when linked to academic access and achievement. For example, women's math performance was found to increase when anticipating an interaction or actually engaging in an interaction with a nonsexist man, compared to a sexist man (Adams et al, 2006;Logel et al, 2009; see also Park, Young, Eastwick, Troisi, & Streamer, 2016). Even across social class lines, intergroup interactions can negatively affect cognitive resources among first-generation college students at elite institutions, yet contact situations that reduce concerns about competency can alleviate cognitive depletion (Johnson, Richeson, & Finkel, 2011).…”
Section: Selves In Contact Addresses Social Inequity: Attitudes Acmentioning
confidence: 99%
“…Park et al (2016) even found women (but not men) were more likely to show worse mathematics performance and less interest in STEM careers to seem desirable when pursuing smarter romantic partners on campus. Women in STEM also face stereotypes regarding appearances and behavior, whereas by appearing too feminine they signal they may not be well suited for science (Banchefsky et al 2016.…”
Section: Stereotypesmentioning
confidence: 99%